Childfree dalam Pernikahan di Era Modern Studi Komparatif Fikih Nikah dan Hukum Perdata di Indonesia: Childfree in Marriage in the Modern Era: A Comparative Study of Marriage Fiqh and Civil Law in Indonesia - Muhammad Ilham; Muhammad Saleh Ridwan; Andi Abdul Hamzah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Childfree in marriage is a contemporary social phenomenon that raises normative debates in the family law system both in the perspective of Islamic law and Indonesian civil law, the decision not to have children is often understood as part of individual freedom and reproductive rights, in other contexts marriage as a legal institution has goals, social functions, and public dimensions that are not fully subject to the private will of the parties. This study aims to analyze and compare the legal status of childfree in marriage, through the formulation of problems regarding: what is the legal status of childfree decisions in marriage jurisprudence according to maqāṣīd al-Syarī’ah, how is the regulation of childfree agreements in family law and what are the meeting points and differences in principles between marriage jurisprudence and civil law related to childfree using normative theological and normative juridical approaches in comparative legal research, analyzed through deductive reasoning and legal syllogism based on maqāṣid shari’ah, prenuptial agreements, and human rights restrictions. The results of this study indicate that, from an Islamic legal perspective, temporary childfree is tolerated as long as it does not negate the right to freedom, while permanent childfree contradicts the purpose of marriage. In Indonesian civil law, prenuptial agreements are not absolute, as they are limited by public order, morality, and the institutional purpose of marriage. The point of agreement between the two lies in the recognition that freedom in marriage is not absolute, but rather limited by social values ​​and institutional goals. The difference is that marital fiqh places offspring as a normative goal that is darūrī, while civil law emphasizes the autonomy of the parties, which is limited by positive law. Thus, reproductive rights in marriage are relational and have normative limits. This research is expected to provide a conceptual contribution in the development of maqāṣid al-Syarī'ah that remains oriented towards the darūrī objectives of sharia. This research is expected to strengthen the integration of Islamic, civil, and human rights law analysis in contemporary marital law studies.